DDRE-10. METABOLIC TARGETING OF HUMAN GLIOBLASTOMA USING 5-AMINOLEVULINIC ACID (ALA)-MEDIATED SONODYNAMIC THERAPY: A FIRST-IN-HUMAN STUDY. (25th March 2021) - Marcus, Stuart; Sanai, Nader
Abstract: Heme biosynthesis is altered in glioblastoma (GBM). Systemic dosing with ALA, the first committed molecule in the heme pathway, results in accumulation of the fluorescent intermediate, protoporphyrin IX (PpIX) only within tumor tissue (Gleolan label, 2019). PpIX is a photosensitizer that is effective in photodynamic therapy (PDT); in recurrent GBM patients, the safety and feasibility of ALA PDT has been demonstrated (Johansson A, et al. Lasers Surg Med 2013;45:225), although the practicality of this strategy in clinical care remains uncertain. Importantly, preclinical models of GBM show that PpIX is also a sonosensitizer and, in combination with transcranial MRI-guided focused ultrasound (MRgFUS), leads to non-ablative cytotoxic effects in vivo (Jeong EJ et al, Ultrasound in Medicine and Biology 2013:38;2143, Suehiro S et al, J Neurosurg 2018: 1377, Wu et al Nature Sci Reports 2019: 9;10465). The Ivy Brain Tumor Center is conducting a first-in-human study of 5-ALA sonodynamic therapy (SDT) for recurrent GBM (NCT 04559685). In this Phase 0/1 clinical trial, nontherapeutic, single-treatment SDT is administered prior to planned tumor resection. A Dose-Escalation Arm varies the power/energy of the MRgFUS while using a fixed time-interval from exposure to surgery. A subsequent Time-Escalation Arm varies the interval between MRgFUS and surgical resection, but fixes the power/energy of the delivered ultrasound. In both Arms, patient tumor tissue is assessed for sonodynamic and pharmacodynamic effects. In each patient, half of the tumor volume is not targeted with SDT and serves as an internal control. This first-in-human study will demonstrate the safety and feasibility of ALA sonodynamic therapy in GBM and may provide the first-ever biological evidence of sonosensitization in a brain tumor patient. If successful, this Phase 0 trial will introduce a new, metabolically-driven, GBM treatment modality that may be applicable to any brain tumor that selectively accumulates PpIX after ALA administration.